Tributação, finanças públicas e política fiscal: uma análise sob a óptica do direito e economia - Seixas, Luiz Felipe Monteiro (2012)
In the Brazilian legal scenario, the study of taxation has traditionally been restricted to positivist analysis, concerned with investigating the formal aspects of the tax legal rule. Despite its relevance to the formation of the national doctrine of tax, such formalist tradition limits the discipline, separating it from reality and the socioeconomic context in which the Tax Law is inserted. Thus, the proposal of the dissertation is to examine the fundamentals and nature of taxation and tax legal rules from the perspective of Law and Economics (Economic Analysis of Law). For this purpose, the work initially reconnects the Tax Law and Science of Finance (or Public Finance) and Fiscal Policy, undertaking not only a legal analysis, but also economic and financial analysis of the theme. The Economics of Public Sector (or Modern Public Finance) will contribute to the research through topics such as market failures and economic theory of taxation, which are essential to an economic approach to Tax Law. The core of the work lies in the application of Law and Economics instruments in the study of taxation, analyzing the effects of tax rules on the economic system. Accordingly, the dissertation examines the fundamental assumptions that make up the Economic Analysis of Law (as the concept of economic efficiency and its relation to equity), relating them to the tax phenomenon. Due to the nature of the Brazilian legal system, any worth investigation or approach, including Law and Economics, could not pass off the Constitution. Thus, the constitutional rules will serve as a limit and a prerequisite for the application of Law and Economics on taxation, particularly the rules related to property rights, freedom, equality and legal certainty. The relationship between taxation and market failures receives prominent role, particularly due to its importance to the Law and Economics, as well as to the role that taxation plays in the correction of these failures. In addition to performing a review of taxation under the approach of Economic Analysis of Law, the research also investigates the reality of Brazilian tax system, applying the concepts developed in relevant cases and issues to the national scene, such as the relationship between taxation and development, the compliance costs of taxation, the tax evasion and the tax enforcement procedure. Given the above, it is intended to lay the groundwork for a general theory of Economic Analysis of Tax Law, contextualizing it with the Brazilian tax system